THE ROLE OF SOCIAL MEDIA IN BUILDING PUBLIC AWARENESS ABOUT SUSTAINABLE DEVELOPMENT - Fatkuroji, Imam; Yulianto, Yulianto; Mukhlis, Maulana (Utan Kayu Publishing, 2025)
The development of information and communication technology, especially social media, has changed the communication landscape significantly. Social media is not only a platform for social interaction, but also an effective tool to build public awareness of global issues, including sustainable development. This paper aims to analyze the role of social media as a strategy in building public awareness about sustainable development. Through a literature review, this study identifies several key roles of social media, namely as a tool for disseminating information, facilitating public dialogue and participation, and shaping public opinion. In addition, this study also examines the challenges faced in the use of social media for sustainable development purposes, such as misinformation, polarization, and digital divide. The results of the paper show that social media has a huge potential to increase public awareness about sustainable development. However, the success of social media utilization is highly dependent on the right communication strategy, cross-sector collaboration, and efforts to overcome existing challenges.